Implementation of Internship Program as A Form of MBKM Learning Activities in Improving Students' Competency - Ida Farida; M. Ardiansyah; Masayu Nila Juwita; Dora Rinova; Soewito Soewito (Nusantara: Jurnal Pendidikan Indonesia, 2022)
In this era of rapid change, students are expected to be able to prepare themselves and continue to hone their abilities. Universities are also required to provide innovative learning processes so that they can help students develop optimal and relevant attitudes, knowledge, and skills. This study aims to describe: 1) Preparation for internships. 2) Implementation of the internship. 3) Evaluation of the Independent Learning Internship Program-Free Campus Public Administration Study Program, University of Bandar Lampung. 4) Reveal how the Merdeka Belajar Kampus Merdeka or commonly called the MBKM internship program improves student competence. Methods of data collection using interviews, observation and documentation.  The data analysis method uses interactive analysis by means of data reduction-data presentation & data verification. The results of this study are: 1) Preparation for internships in the Administration study program is carried out well, students have carried out registration procedures according to the provisions, DPL (field supervisor) also provides debriefing for students before being deployed to partner locations. 2) The implementation of the internship program for students is in accordance with the guidelines for the Independent Learning Independent Campus internship guidebook. 3) Stakeholders (partners) and DPL provide a joint evaluation at the end of the program. 4) Implementation of the MBKM internship program strengthen student competencies.